Education 3590. Moral education. No. 14. Interview with Dr. Bryan Hartmann. - Magsino, Romulo F. (Teacher)
Dr. Romulo Magsino interviews Dr. Bryan Hartmann on cognitive theory and moral development. An ETV production.